RecStore - Recommending Stores for Shopping Mall Customers - Silva, Diogo Vinícius de Sousa; Silva, Renato de Santana; Customers, Frederico Araújo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Today, mobility is a key feature in the new generation of Internet, which provides a set of custom services through numerous terminals. Smartphones, for example, are a tendency and almost mandatory to anyone living in an urban and modern context. Most of the developed cities have at least one shopping mall full of mobile devices users. These shopping malls provide a number of stores, and people tend to have difficult in finding what they really need. This paper proposes a solution called RecStore. RecStore is a recommendation model to assist customers in reaching what they consider relevant at malls. The recommendation model considers user activities, 330 stores, 30 users and 3 baseline models. The precision, recall and f-measure improved at rates of 118%, 70% and 88% respectively in comparison to the second best model of each metric. Additionally, a mobile application — called InMap — was implemented based on RecStore.